Statistics-Based Chain Code Compression with Decreased Sensitivity to Shape Artefacts - Podgorelec, David; Nerat, Andrej; Žalik, Borut (Informatica, 2021)
Chain codes compactly represent raster curves, but there is still a lot of room for improvement by means of data compression. Several statistics-based chain code compression techniques assign shorter extra codes to frequent pairs of consecutive symbols. Here we systematically extend this concept to patterns of up to six symbols. A curve may be represented by any of the exponentially many overlapped chains of codes, and the dynamic programming approach is proposed to determine the optimal chain. We also propose utilization of multiple averaged hard coded pseudo-statistical models, since the exact statistical models of individual curves are often huge, and they can also significantly differ from each other. A competitive compression efficiency is assured in this manner and, as a pleasant side effect, this efficiency is less affected by the curve’s shape, rasterization algorithm, noise, and image resolution, than in other contemporary methods, which surprisingly do not pay any attention to this problem at all.